Caracterização do extrato amiláceo nativo e modificado quimicamente da semente de abacate (Persea americana Mill) - Silva, Izis Rafaela Alves (2011)
Recent years have seen a significant increase in demand for starches with specific properties, leading to the modification of these properties in order to get ideal for your application. The objective of this study was to obtain information about the properties of starch from avocado seed cv. "Butter" and submit it to the modification by acetylation and cross-linking, to provide rheological characteristics applicable in obtaining food. The native starch showed starch content of 74.47 % in the physical-chemical analysis and performance of the extraction process used in 11.36%. The degree of substitution (GS) of native starch by acetylation was 0.007 and 0.006 for cross-linking. The native starch granules and had modified oval and circular, their dimensions ranging from 26 to 26.34 μm for the smaller diameter and 35.75 to 36.85 μm for the larger diameter. The pattern of crystallinity shown by X-ray diffraction was type C. The swelling power and solubility at temperatures 75, 85 and 95 °C was maximum for the native starch and modified by acetylation in relation to cross-linking. The changes reduced the ability of native starch hydrophilic and hydrophobic increased their capacity. The native starch gel showed an opaque folder, and with a tendency to retrogradation, modified with acetic anhydride showed no difference compared to the native whereas modification by cross-linking improved the clarity of the folder and decreased the tendency to retrogradation. Stability to freezing and thawing all samples released water in the first cycle, but with each passing day there was a decrease in syneresis. The acetylated starch did not differ from native in the analysis of viscosity has low viscosity and a greater tendency to retrogradation. The starch is modified by cross-linking showed efficacy by introducing cross-links in native starch granule and its peak viscosity was well below the value obtained in native, just had a lower tendency to retrogradation. In Differential Scanning Calorimetry (DSC) was an initial decrease in temperature for starch modified by cross-linking, and all samples did not differ significantly in peak temperature.